Tanya Tinker and the Gizmo gang : a lift-the-flap discovery book. (Alexandria, Va. : Time-Life for Children, 1992)
While tracking down the owner of a list they found, three children discover how many things work. Liftable flaps reveal some of their "finds."
Keywords: Toy and movable books; Mystery and detective stories